Environmental Protection in the Era of Omnibus Law - Nasikhin, Rodhatul; Ihsan, Ahmad Nuril (JASSP, 2022)
Indonesia is not a green constitution implementing country that explicitly states the Environmental Law in the constitution. In an environment that is not recognized as a subject of law, the guarantee of its protection relies on the dominating regime’s will. This paper is aimed to identify and analyze environmental protection since Omnibus Law on Job Creation was enacted. The analysis technique used in this paper is normative juridical. The result of this research found that Omnibus Law enforcement is weakening against environmental protection in Indonesia and is incompatible with the sustain theory/principal of the environmental management that has been established with the characterization of profit-oriented. The weakening of the environment includes the environmental permits sector which is replaced by environmental agreement, the absence of criminal penalty that may lead to the absence of deterrent effect as well as people’s control rights. Increasing economic growth investment does not necessarily mean sacrificing environmental protection. This study suggests the government formulate a proper and balanced regulation between economic improvement and environmental spirit.